Resources and Innovation Strategies in Entrepreneurship in Micro, Small and Medium Enterprises (MSMEs) - Antara, Radittya Mahasputra; Andaryanto; Rahayu, Wening Patmi; Winarno, Agung (PT Maju Malaqbi Makkarana, 2025)
Micro, small and medium-sized enterprises (MSMEs) are vital to the Indonesian economy, both in Indonesia and Southeast Asia. Small and medium-sized businesses (MSMEs) play an important role in economic growth and job creation in a country. Innovation in products, services, and business strategies is crucial in the context of globalization and intensified competition. Innovation is critical to the growth of MSMEs as the differences in access to resources between MSMEs and large enterprises pose significant challenges. Innovation strategies enable firms to maximize their resources and become more competitive. In this article, the perspectives of Resource-Based View theory (RBV) and Resource-Advantage theory (R-A theory) are discussed in order for businesses to compete with other businesses, both theories relate to maximizing resources and focusing on innovation. As market conditions are always changing, businesses must be competitive. With innovative strategies, MSMEs can respond to rapid market transformation and evolving consumer desires. Intellectual and human resources, financial resources, technological resources, and organizational resources are important resources owned by MSMEs to support them in innovating to achieve sustainable business goals. MSMEs face several issues, such as access and financial constraints, effects of digitalization, financing mechanisms, and policy implications that can be further researched.